2008
DOI: 10.1523/jneurosci.1533-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Functional Stability of Retinal Ganglion Cells after Degeneration-Induced Changes in Synaptic Input

Abstract: Glutamate released from photoreceptors controls the activity and output of parallel pathways in the retina. When photoreceptors die because of degenerative diseases, surviving retinal networks are left without their major source of input, but little is known about how photoreceptor loss affects ongoing synaptic activity and retinal output. Here, we use patch-clamp recording and two-photon microscopy to investigate morphological and physiological properties of identified types of ON and OFF retinal ganglion cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
269
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 197 publications
(304 citation statements)
references
References 44 publications
34
269
1
Order By: Relevance
“…By P30 -P40, the one or two rows of photoreceptor cell bodies that remain (Carter-Dawson et al, 1978;Lin et al, 2009) do not appear to maintain their sensitivity to light (Strettoi et al, 2002), although they remain functionally connected with bipolar cells (Busskamp et al, 2010). In response to this sensory deafferentation, a marked increase in the spontaneous firing rates of ganglion cells has been observed previously (Ye and Goo, 2007;Margolis et al, 2008;Stasheff, 2008). To determine whether such activity arises in specific retinal circuits, we first recorded spike activity from single ganglion cells (P30 -P70) and subsequently characterized their morphologies.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…By P30 -P40, the one or two rows of photoreceptor cell bodies that remain (Carter-Dawson et al, 1978;Lin et al, 2009) do not appear to maintain their sensitivity to light (Strettoi et al, 2002), although they remain functionally connected with bipolar cells (Busskamp et al, 2010). In response to this sensory deafferentation, a marked increase in the spontaneous firing rates of ganglion cells has been observed previously (Ye and Goo, 2007;Margolis et al, 2008;Stasheff, 2008). To determine whether such activity arises in specific retinal circuits, we first recorded spike activity from single ganglion cells (P30 -P70) and subsequently characterized their morphologies.…”
Section: Resultsmentioning
confidence: 88%
“…The dendrites of ON and OFF ganglion cells stratify in the proximal (0 -60%) and distal (60 -100%) layers of the IPL, respectively, whereas those of ON-OFF cells stratify in both layers. Post hoc morphological analysis revealed that the dendritic stratification patterns of rd1 ganglion cells were maintained at a stage when photoreceptors are almost completely lost (Margolis et al, 2008;Mazzoni et al, 2008), allowing for their classification using similar criteria as that for wt ganglion cells. Examples of Neurobiotin-filled ON, OFF, or ON-OFF ganglion cells in the rd1 retina are illustrated in Figure 1 A (top).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations